Bilateral Radial Club Hands at the Komfo Anokye Teaching Hospital, Kumasi, Ghana: A Case Report. - Dominic Konadu-Yeboah; Peter Konadu; Yifieyeh Abiboye C; Ampem-Darkwa; Zainab Schumacher (Journal of Preventive Medicine And Care, 2019)
Radial Club Hand (RCH) is a rare and complex congenital disorder of the pre-axial border of the upper extremity. It is a congenital longitudinal radial ray deficiency which presents as radial deviation of the hand and distal forearm in the shape of a golf club 12. Radial ray deficiency (the most common type of longitudinal failure of formation) is a spectrum of malformations affecting the structures of the radial side of the forearm, including hypoplasia of the bones, joints, muscles, tendons, ligaments, nerves and blood vessels. The thumb dysfunction, wrist instability and short upper extremity that accompany this condition can cause significant functional impairment particularly in patients with bilateral involvement. Thus, the performance of activities of daily living such as accomplishing personal hygiene, fastening buttons and zippers becomes challenging 3.
Keywords: complex congenital disorder